Economic Geography and the Financial Crisis: Full Steam Ahead? - Christopher Muellerleile (The Professional Geographer, 2014)
This article considers whether the growing theoretical and methodological diversity or pluralistic nature of economic geographycontributes to its lack of engagement outside the discipline and academy. Although we are enthusiastic about the vibrancy thispluralism brings, we also speculate that it contributes to the discipline’s tendency to fall short of significantly impacting keydebates in the social sciences. In particular, we consider the disciplinary challenges to influencing mainstream debates overfinancialization and the recent financial crisis and the recurring lament that economic geography “misses the boat” by failingto significantly impact key scholarly and policy issues. Specifically, we suggest that methodological and theoretical diversity,local contextualization, and relational analysis, all of which we support as vital to the discipline, make it difficult to isolate adisciplinary core. We conclude that pluralism produces a vibrant discipline with unique explanatory power but that it also hasimportant impacts on the design, execution, and influence of geographers’ research outside the discipline.